Blunt Transection of the Entire Anterolateral Abdominal Wall Musculature Following Seatbelt-Related Injury - Hohyun Kim; Jae Hun Kim; Gil Hwan Kim; Hyun-Woo Sun; Chan Ik Park; Sung Jin Park; Chan Kyu Lee; Suk Kim (Journal of Trauma and Injury)
Traumatic abdominal wall hernias (TAWHs) are uncommon and the incidence of this, which is rarely encountered in clinical practice, has been estimated at 1%. Furthermore, blunt transection of the entire abdominal wall musculature caused by seatbelt is a very rare complication. We report a case of adult with a complete disruption of the entire anterolateral abdominal wall muscle following the seatbelt injury. A 32-year-old male was wearing a seat belt in a high speed motor vehicle collision. Abdominal computed tomography (CT) scan revealed the complete disruption of bilateral abdominal wall musculatures including TAWH without visceral injury. However, injuries of small bowel and sigmoid colon were observed in the intra-operative field. The patient underwent the repair by primary closure of the defect with absorbable monofilament sutures. This case suggests that especially in TAWH patients, even if a CT scan is normal, clinicians should keep the possibility of bowel injury in mind, and choose a treatment based on the clinical findings.